Cradle of Liberty : Race, the Child, and National Belonging from Thomas Jefferson to W. E. B. Du Bois - Levander, Caroline Field, 1964- (Book collections on Project MUSE., 2006)
Argues that from the late eighteeneth century through the early twentieth, American literary and political texts used the figure of the child to represent U.S. national belonging.